Double First Metatarsal and Akin Osteotomy for Severe Hallux Valgus. (October 2015) - Al-Nammari, Shafic Said; Christofi, Theodoros; Clark, Callum
Background: The technique of double first metatarsal osteotomies was first developed in response to the high frequency of recurrence noted in the treatment of severe adolescent congruent hallux valgus deformities. The concept behind the use of this technique is that it allows the individual correction of each component of the deformity. We have modified the technique for use in adult hallux valgus where the majority of deformities are incongruent deformities and the distal chevron osteotomy is used primarily for its additional translational properties rather than purely to correct the distal metatarsal articular angle (DMAA). We report on a series of double first metatarsal osteotomies (basal opening wedge and distal chevron osteotomy) with Akin osteotomy in the treatment of moderate to severe adult hallux valgus deformity. Methods: All patients presenting to our institution with a hallux valgus deformity and treated with this procedure between 2008 and 2013 with a minimum of 1 year of follow-up were identified. Data were obtained through review of case notes, electronic charts, and digital imaging. A total of 50 feet in 48 patients underwent double first metatarsal osteotomy with Akin osteotomy. Three patients were excluded due to loss to follow-up, leaving 47 feet in 45 patients with a mean follow-up of 45 months (range, 14-60 months). Of these 43 (96%) were female and the mean age was 56 years (range, 35-70 years). Results: The mean preoperative hallux valgus angle (HVA), intermetatarsal angle (IMA), DMAA, sesamoid position, and lateral first metatarsotalar angle were 42 degrees (range, 32-52 degrees), 18 degrees (range, 6-26 degrees), 12 degrees (range, 4-26 degrees), stage 6 (range, 4-7), and 2 degrees of dorsiflexion (range, 20 degrees of dorsiflexion to 4 degrees of plantar flexion), respectively. The mean postoperative HVA, IMA, DMAA, sesamoid position, and lateral first metatarsotalar angle were 7 degrees (range, 2 to 24 degrees), 4 degrees (range, 4-14 degrees), 6 degrees (range, 10-22 degrees), stage 2 (range, 1-5) and 6 degrees of plantar flexion (range, 8 degrees of dorsiflexion to 18 degrees of plantar flexion), respectively. The osteotomies consolidated at a mean of 7 weeks (range, 5-9 weeks). There were no cases of delayed union or nonunion. Of the cohort, 45 (96%) stated that they were satisfied overall with the results of their surgery and would have it again. The mean postoperative summary index Manchester-Oxford Foot Questionnaire (MOXFQ) score was 12.9 (range, 0-60.9) out of 100 at a mean follow-up of 45 months (range, 14-60 months). For the minority of cases, 8 (17%), that had preoperative scoring, the summary index MOXFQ score was 73.7 (range, 29.7-100). Conclusions: The double first metatarsal osteotomy (basal opening wedge and distal chevron osteotomy) with Akin osteotomy provides powerful correction and facilitates correction of the individual components of the hallux valgus deformity. The individual osteotomies that make up this procedure are familiar to the majority of foot and ankle surgeons, thus limiting the associated learning curve. Level of Evidence: Level IV, retrospective case series.